The Effects of Exercise Training on Glucose Homeostasis and Muscle Metabolism in Type 1 Diabetic Female Mice - Caitlin C. O’Neill; Erica J. Locke; Darren A. Sipf; Jack H. Thompson; Erin K. Drebushenko; Nathan S. Berger; Brooke S. Segich; Stephen C. Kolwicz (Metabolites, 2022)
Although exercise training is an important recommendation for the management of type 1 diabetes (T1D), most of the available research studies predominantly focus on male subjects. Given the importance of sex as a biological variable, additional studies are required to improve the knowledge gap regarding sex differences in T1D research. Therefore, the purpose of this study was to examine the role of exercise training in mediating changes in glucose homeostasis and skeletal muscle metabolism in T1D female mice. Female mice were injected with streptozotocin (STZ) to induce T1D. Two weeks after STZ injection, control (CON) and STZ mice were exercise trained on a treadmill for 4 weeks. Aerobic exercise training failed to improve glucose tolerance, prevent the decrease in body weight and adipose tissue mass, or attenuate muscle atrophy in T1D female mice. However, insulin sensitivity was improved in T1D female mice after exercise training. Aerobic exercise training maintained skeletal muscle triglyceride content but did not prevent depletion of skeletal muscle or liver glycogen in T1D mice. Gene expression analysis suggested that T1D resulted in decreased glucose transport, decreased ketone body oxidation, and increased fatty acid metabolism in the skeletal muscle, which was not altered by exercise training. These data demonstrate that 4 weeks of aerobic exercise training of a moderate intensity is insufficient to counteract the negative effects of T1D in female mice, but does lead to an improvement in insulin sensitivity.